FRI0403 HIGH BASELINE PATIENT'S COMPARED WITH EVALUATOR'S GLOBAL ASSESSMENT IS ASSOCIATED WITH LOWER RETENTION AND REMISSION RATES OF FIRST TNF INHIBITOR IN AXSPA PATIENTS – DATA FROM THE EUROSPA COLLABORATION. (June 2019) - Michelsen, Brigitte; Ørnbjerg, Lykke; Loft, Anne Gitte; Sexton, Joseph; Ciurea, Adrian; Mann, Heřman; Eklund, Kari; Yazici, Ayten; Santos, Maria Jose; Askling, Johan; Rotar, Ziga; Gudbjornsson, Björn; et al.
Abstract : Background: Discordance between baseline patient's and evaluator's global assessment of disease activity is common. 1 However, the impact of such discordance on retention and remission rates of TNF inhibitor (TNFi) therapy in axial spondyloarthritis (axSpA) patients remains unexplored. Objectives: To assess the impact of baseline discordance, defined as "patient's minus evaluator's global assessment of disease activity" (ΔPEG), on retention and remission rates of first TNFi in female and male axSpA patients across Europe. Methods: AxSpA patients from 10 European registries participating in the European Spondyloarthritis Research Network Collaboration (EuroSpA) were included. Retention rates after 6/12/24 months' treatment with first TNFi were assessed with Kaplan-Meier analyses, with comparison between baseline ΔPEG quartiles with log rank test, stratified by gender. Proportions of patients in BASDAI remission (≤2) and ASDAS inactive disease (<1.3) after 6/12/24 months for different ΔPEG quartiles were compared with Chi-square test, stratified by gender. Results: A total of 9013 axSpA patients were included. Mean(SD) age for women(n=3639)/men(n=5374) were 42.7(12.0)/41.7(12.0) years, disease duration 5.1(7.4)/6.9(8.7) years, median(25-75 percentiles) baseline ΔPEG 20(3-42)/15(0-37) mm. TNFi retention rates and proportions of patients achieving BASDAI≤2 and ASDAS<1.3 after 6/12/24 months were lower for higher quartiles of ΔPEG (table, figure). Conclusion: In patients receiving their first TNFi, high baseline patient's compared with evaluator's global assessment is negatively associated with retention rates as well as proportions of patients achieving BASDAI remission and ASDAS inactive disease after 6, 12 as well as 24 months follow-up, both in female and male axSpA patients. References: [1] Lindström, et al., J Rheumatol2015;42:1781-5. Acknowledgement: Novartis Pharma AG and IQVIA for supporting the EuroSpA collaboration Disclosure of Interests: Brigitte Michelsen Grant/research support from: Unrestricted grant: Novartis, Consultant for: Novartis, UCB, Lykke Ørnbjerg Grant/research support from: Unrestricted grant: Novartis, Anne Gitte Loft: None declared, Joseph Sexton: None declared, Adrian Ciurea Consultant for: AbbVie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Heřman Mann Consultant for: Pfizer, Eli Lilly, Sanofi, Speakers bureau: AbbVie, Roche, Pfizer, MSD, Eli Lilly, Sanofi, Kari Eklund: None declared, Ayten Yazici: None declared, Maria Jose Santos: None declared, Johan Askling Grant/research support from: Karolinska Institutet (JA) has or has had research agreements with the following pharmaceutical companies, mainly in the context of the ATRIS national safety monitoring programme for rheumatology biologicals: Abbvie, BMS, MSD, Eli Lilly, Pfizer, Roche, Samsung Bioepis, and UCB., Consultant for: Karolinska Institutet has received remuneration for JA participating in ad boards arranged by Lilly, Novartis, and Pfizer., Ziga Rotar: None declared, Björn Gudbjornsson: None declared, Manuel Pombo-Suarez: None declared, Catalin Codreanu: None declared, Irene van der Horst-Bruinsma Grant/research support from: MSD, Pfizer, AbbVie, Consultant for: Abbvie, UCB, MSD, Novartis, Speakers bureau: BMS, AbbVie, Pfizer, MSD, Eirik kristianslund: None declared, Michael Nissen Consultant for: AbbVie, Lilly, Novartis, and Pfizer, Karel Pavelka: None declared, Nina Trokovic: None declared, Nevsun Inanc: None declared, Elsa Vieira-Sousa Grant/research support from: MSD, Novartis, Daniela Di Giuseppe: None declared, Matija Tomsic: None declared, Arni Jon Geirsson: None declared, Ruxandra Ionescu: None declared, Marleen van de Sande Grant/research support from: Research support from Janssen, Novartis, Eli Lily, Consultant for: Received consultation fees from Abbvie and Novartis, Florenzo Iannone Consultant for: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, AbbVie, MSD, BMS, Novartis, Lilly, UCB outside this work, Speakers bureau: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, AbbVie, MSD, BMS, Novartis, Lilly, UCB outside this work, Carlos Sánchez-Piedra: None declared, Gareth T. Jones Grant/research support from: Have received research grants (not current) from Abbvie and Pfizer. Have received research grants (not current) from the British Society for Rheumatology, who received the funds from Abbive, Pfizer and UCB. Have received research grant (current) from the British Society for Rheumatology, who received the funds from Celgene., Lise Hyldstrup: None declared, Niels Steen Krogh: None declared, Merete L. Hetland Grant/research support from: BMS, MSD, AbbVie, Roche, Novartis, Biogen, Pfizer, Consultant for: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck, Samsung Bioepis, Mikkel Ǿstergaard Grant/research support from: Abbvie, Celgene, Centocor, Merck, Novartis, Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Speakers bureau: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB